Do Trust and Waqf Knowledge Able to Explain Waqf Intention in Livestock Sector? Empirical Evidence from Indonesia - Majid, Rifaldi; Fauziyyah, Neneng Ela; Ramdani, Ramdani; Friantoro, Dian; Indrawan, Imam Wahyudi (UIN Sunan Kudus, 2024)
This study examines what waqf knowledge and trust influence waqif's intentions to donate to the livestock sector. Extending the Theory of Planned Behavior, this research adopts a quantitative approach. Data was collected through online questionnaires for respondents who had previously donated waqf. This research utilizes Smart-PLS version 4 along with Partial Least Square-Structural Equation Modelling. The findings of this research indicate that subjective norms, attitude toward behavior, trust, and knowledge about waqf significantly affect the intention to perform waqf specifically for the livestock sector. Meanwhile, perceived behavioral control shows the opposite result. In addition, trust and waqf knowledge are the variables with the most significant influence on waqf intentions. This research provides insight to waqf regulators and nazhir who have a particular waqf program for the livestock sector to continue to increase literacy and education about waqf and how it plays a role in maintaining national food security. This research also not only reinforces the importance of the waqf sector but also has implications for the livestock sector concerning sources of financing for breeders and efforts to utilize waqf land as grazing fields